Corporate Social Responsibility Strategies and University Goal Achievement in Public Universities in Kwara State, Nigeria - Medupin, Johnson Abiodun; Olaifa, Adeseko Sunday; Ajadi, Bashiru Ibrahim; Ebenezer, Kayode Olumuyiwa; Shittu, Afeez Adeshina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The study investigates the relationship between corporate social responsibility strategies and university goal achievement in Kwara State, Nigeria public universities. The research used a correlational design and a multi-stage sampling technique to select 593 respondents, including 465 academic staff and 128 management staff. The questionnaires, Corporate Social Responsibility Strategies Questionnaire and University Goal Achievement Questionnaire were used for data collection. The findings revealed that universities moderately implemented direct corporate philanthropy strategies for CSR, with a low degree of strategic relationship strategy and limited multi-stakeholder strategy adoption. The objective achievement was moderately high. The study suggests that corporate organisations providing CSR to Kwara State's public universities should strengthen their CSR strategies, including direct corporate philanthropy, strategic partnerships, and multi-stakeholder initiatives, to boost university goal achievement. The study also suggests businesses should enhance their application and embrace research ideas when running CSR initiatives at universities.